The Promotion of Beekeeping and Bee Product and By-Product Development at PSAU, Philippines - de Jesus, Norman (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2020)
The study is divided into two components, namely; the beekeeping status and contribution of bees as pollinators and the development of its by-products. The first component is on documentation of existing beekeeping activity and honey utilization in Region III; Inventory of bee plants surrounding Mt. Arayat and the contribution of the honeybee as pollinators to selected tropical fruit trees and vegetable crops. The second component, which is on the development of products and by-products came up with a honey wine formulation and eight wellness products. The general objective of this project is to promote beekeeping, its products, and by-products developed among various communities in the vicinity of Mt. Arayat and nearby municipalities of Pampanga. Beekeepers are members of the Beekeeper Association, Luzon Chapter. The type of race usually found in the research places is Apis millifera where the number of colonies of the Beekeepers ranges from 4 to 48. The farm size for beekeeping ranges from 1000 to 5000sq.m. Beekeepers observed proper hive placement, density, water, and management. As to training needs the beekeepers said that they need training on the global trends in beekeeping, a quality race of bees (queen) and packaging technology for honey. Eight forest trees, 12 vegetables, five field crops, 13 fruit trees, six ornamental plants, and four wild plants have so far been identified and were found within PAC surroundings and vicinity of Mount Arayat. These plants varied in their flowering time which makes them good sources of nectar and pollen all year round for the honeybees. There are plants bearing either nectar or pollen, and there are also plants that possess both the nectar and pollen. The study showed that honeybees could affect the fruit size and harvest of cashew, squash, cucumber, and tamarind fruits. The honey wine developed is very much acceptable in terms of appearance, aroma, and taste. The wellness products were very effective in the specific study conducted such as acne, wound healing, and rashes, among others. There were about 500 individuals who were afforded with either of the following technology transfer: hands-on training, seminar, orientation and the likes